2022
DOI: 10.1016/j.psj.2021.101541
|View full text |Cite
|
Sign up to set email alerts
|

Effects of naturally oxidized corn oil on inflammatory reaction and intestinal health of broilers

Abstract: This study was conducted to investigate the effects of naturally oxidized corn oil on the inflammatory reaction and intestinal health of broilers. Total 450, one-day-old Arbor Acres male broilers were randomly divided into 5 treatments with 6 replicate cages (15 birds in each replicate cage). The dietary treatment array consisted of the varying ratio of nonoxidized corn oil to naturally oxidized corn oil from 0:100, 25:75, 50:50, 75:25, and 100:0, respectively. The experimental period was 42 d. Serum, jejunum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Additionally, epithelial cells can have levels of NT proteins with cell function deficits that vary by diet in the absence of detectable infectious disease [ 26 , 27 ]. Oxidative/nitration protein and lipid damage has been generated in chickens simply by low levels of partially oxidized corn oil or polyunsaturated fatty acids being in the diet [ 38 ]; similarly, that oxidized oil-induced inflammation was relieved with the addition of the flavonoid antioxidant quercetin to the chicken diet [ 39 ]. Mitigation of gut dysfunction by reducing inflammation is a goal of both human and veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, epithelial cells can have levels of NT proteins with cell function deficits that vary by diet in the absence of detectable infectious disease [ 26 , 27 ]. Oxidative/nitration protein and lipid damage has been generated in chickens simply by low levels of partially oxidized corn oil or polyunsaturated fatty acids being in the diet [ 38 ]; similarly, that oxidized oil-induced inflammation was relieved with the addition of the flavonoid antioxidant quercetin to the chicken diet [ 39 ]. Mitigation of gut dysfunction by reducing inflammation is a goal of both human and veterinary medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al ( 28 ) found that the reduction of claudin-1, ZO-1, and ZO-2 by SeNPs might reduce the sites to attaching the pathogen bacteria. Meanwhile, the products of oxidative stress also increased intestinal permeability by decreasing expression levels of tight junction proteins ( 19 , 37 ). The increase of Se in the diet reduced the influence of heat stress on the integrity of the intestinal barrier by reducing oxidative stress products ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under the Leica microscope (DMI803250593, Heidelberg, Germany), the intestinal villus height (VH) and crypt depth (CD) were measured by randomly selecting 10 intact villi for every bird. The density of goblet cells was expressed as the number of goblet cells per 100 μm ( 19 ). The method was calculated by randomly selecting 10 intact villi and measuring the number of goblet cells in corresponding villi under the mid-villi area (100 μm in length) ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal experimental studies, oxidative stress models are generally constructed by adding oxidized oils, including oxidized fish oil, oxidized corn oil, and oxidized soybean oil. In a test of the effect of using different ratios of oxidized corn oil on broiler chickens, Zhang et al found that serum and jejunal antioxidant factors showed a significant quadratic response with the increase in oxidized oil concentration [ 37 ]. Another trial using oxidized tuna oil as a stressor found that dietary oxidized tuna oil increased some lipid peroxidation markers in trout [ 38 ].…”
Section: Discussionmentioning
confidence: 99%